2001
DOI: 10.1111/j.1600-0447.2001.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen withdrawal associated psychoses

Abstract: Objective: Oestrogen withdrawal has been hypothesized as playing a causal role in puerperal psychoses. However, oestrogen withdrawal exists in conditions others than puerperium. We searched the published case reports where a decrease in oestrogen levels not occurring during puerperium was associated with a psychotic disorder, in order to evaluate the relevance of this hypothesis. These cases were defined as oestrogen withdrawal associated psychoses. Method: A systematic research of the literature was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…The postpartum period is the time of highest vulnerability for risk, with relapse rates exceeding 50% in mixed cohorts . Several factors have been proposed to explain the increased susceptibility to affective episodes associated with pregnancy/postpartum including, but not limited to, medication non‐adherence, alterations in drug pharmacokinetics, changes in reproductive hormonal concentrations, and adverse effects on sleep hygiene/architecture .…”
Section: Resultsmentioning
confidence: 99%
“…The postpartum period is the time of highest vulnerability for risk, with relapse rates exceeding 50% in mixed cohorts . Several factors have been proposed to explain the increased susceptibility to affective episodes associated with pregnancy/postpartum including, but not limited to, medication non‐adherence, alterations in drug pharmacokinetics, changes in reproductive hormonal concentrations, and adverse effects on sleep hygiene/architecture .…”
Section: Resultsmentioning
confidence: 99%
“…We were also unable to examine the associations of postpartum psychiatric illness and other reproductive events, such as endocrine function or postpartum hormonal contraceptive use. 13 Other unmeasured and possibly important variables that would have strengthened our study include sleep quality, 9,10 and partner and/or general social support. 1,11,21 Our findings of few associations between routinely documented variables and postpartum psychosis do not precludein fact, they may encouragethe future examination of the social and environmental factors that may exacerbate postpartum psychological risks in vulnerable women.…”
Section: Discussionmentioning
confidence: 99%
“…6 It has been positively associated with primiparity, 2,7 older maternal age, 8 sleep loss, 9,10 low social support, 8,11 the use of prescribed drugs, 12 and estrogen withdrawal. 13 It is most strongly and consistently associated with a pre-conception history and family history of psychosis. [1][2][3]6,[14][15][16][17][18] Harlow et al 14 reported that pre-conception psychotic or bipolar illness significantly increased the likelihood of postpartum hospitalisation for psychotic disorder, with increased likelihood among women with more recent, more frequent, and lengthier pre-conception psychiatric hospitalisations.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the abrupt hormonal withdrawal after delivery may trigger relapse in vulnerable women. 1 The value of estrogen in prevention and treatment of post-partum affective disorder is suggested by some articles. 2,3 We here report a beneficial effect of hormone replacement therapy (HRT) in treatment-resistant post-partum mania.…”
mentioning
confidence: 99%